METHODS OF DETECTING circRNA (2020)
The present disclosure relates to a method to detect or measure circRNAs in a biological sample of a subject. In particular the present disclosure is directed to a method for diagnosing a neurological, neurodegenerative, or neuropathological disease such as Alzheimer's disease, in a subject and comprises the steps of-determining the level of one or more circRNA in a sample of a biological sample of said subject.